The effect of good governance on the success of the implementation of performance-based budgeting in Balai Besar Pelaksanaan Jalan Nasional V Surabaya - Auliarahma .; Titis Puspitaningrum Dewi Kartika (STIE Perbanas Surabaya, 2014)
This study aims to see the effect of good governance on the success of the implementation of performance-based budgeting. Type of data used in this research is primary data in the form of questionnaires. The sampling technique in this study uses non probability sampling in the form of convenience sampling. The results show that the variable of rule of law affects the success of the implementation of performance-based budgeting; the variable of accountability, transparency and participation affects the success of the implementation of performance-based budgeting; the variable of technical and managerial competence of employees affects the success of the implementation of performance-based budgeting; the variable of organizational capacity affects the success of the implementation of performance-based budgeting, while the variable of information technology does not affect the success of the implementation of performance- based budgeting.